The influence factors of medical professionalism: A stratified-random sampling study based on the physicians and patients in ambulatory care clinics of Chengdu, China. Issue 43 (October 2016) - Lin, Yifei; Yin, Senlin; Lai, Sike; Tang, Ji; Huang, Jin; Du, Liang
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: As the relationship between physicians and patients deteriorated in China recently, medical conflicts occurred more frequently now. Physicians, to a certain extent, also take some responsibilities. Awareness of medical professionalism and its influence factors can be helpful to take targeted measures and alleviate the contradiction. Through a combination of physicians' self-assessment and patients' assessment in ambulatory care clinics in Chengdu, this research aims to evaluate the importance of medical professionalism in hospitals and explore the influence factors, hoping to provide decision-making references to improve this grim situation. From February to March, 2013, a cross-sectional study was conducted in 2 tier 3 hospitals, 5 tier 2 hospitals, and 10 community hospitals through a stratified-random sampling method on physicians and patients, at a ratio of 1/5. Questionnaires are adopted from a pilot study. A total of 382 physicians and 1910 patients were matched and surveyed. Regarding the medical professionalism, the scores of the self-assessment for physicians were 85.18 ± 7.267 out of 100 and the scores of patient-assessment were 57.66 ± 7.043 out of 70. The influence factors of self-assessment were physicians' working years ( P = 0.003) and patients' complaints ( P = 0.006), whereas the influence factors of patient-assessment were patients' ages ( P = 0.001) and their physicians' working years ( P  < 0.01) and satisfaction on the payment mode ( P = 0.006). Higher self-assessment on the medical professionalism was in accordance with physicians of more working years and no complaint history. Higher patient-assessment was in line with elder patients, the physicians' more working years, and higher satisfaction on the payment mode. Elder patients, encountering with physicians who worked more years in health care services or with higher satisfaction on the payment mode, contribute to higher scores in patient assessment part. The government should strengthen the medical professionalism for young physicians and improve the payment mode.